An Investigation of the Tender Nut Potential of Diverse Coconut (Cocos nucifera L.) Varieties/Forms in Sri Lanka - Perera, S. A. C. N.; Ekanayake, G. K.; Herath, H. M. N. B. (International Coconut Community Journal, 2015)
There is a rising demand in the world for coconut water as a healthy natural beverage. Different coconut varieties are used in different countries to be processed as a natural drink. The coconut form “King coconut” has long been used in Sri Lanka as the ideal coconut variety for this purpose. However, with the expansion in the local and export beverage coconut market, the supply does not meet with the demand at present. Therefore, this study was conducted to identify potential coconut varieties/forms mainly relating to the yield of beverage. The study was conducted in the main coconut triangle and Southern Sri Lanka. Eleven coconut forms, namely, King coconut and Bothal thembili in the variety Aurantiaca, Red, Yellow, Green and Brown dwarf and Murusi in the variety Nana, Bodiri, Dothalu, and Sri Lanka tall. These are included in the variety Typica along with Nipol, which is a natural hybrid being identified to be suitable as beverage coconuts. Out of them the yielding ability was high in King coconut, Red dwarf andYellow dwarf while Bodiri, Nipol and Dothalu fared well. Many coconut forms suitable for beverage purpose were observed to be having seasonality in nut production. Ensuring adequate soil fertility and prevention of water deficit over prolonged periods were observed to help sustain yield and reduce seasonality in bunch emission. There were no large scale plantations for beverage coconuts in Sri Lanka, and the entire collection was from home gardens and very small scale holdings. It is recommended to establish medium scale holdings with coconut forms having high yield potential as identified in the current study, with proper management guidance to ensure a steady supply of beverage coconuts to the local as well as export market.